Caracterización del procesamiento antigénico y la persistencia de la proteína Lumazina Sintasa de Brucella spp. - Rossi, Andrés Hugo (2016)
Brucella spp. Lumazine Synthase (BLS) is a highly immunogenic and stable homodecameric protein which has the ability to activate dendritic cells. It can be used to generate decameric chimeras by adding the peptide sequence to the monomer. Immunization with these chimeras induces a long-lasting and strong humoral response against BLS and the peptide; by these means BLS can be used as a carrier. In this work we aimed to study the persistence of BLS in the immunized animal and how this particular protein is processed as an antigen, as two of the main aspects that may play a role in developing the above mentioned humoral immune response. We were able to show that BLS associates with the plasma membrane of dendritic cells, enters the cell via macropinocytosis and co-localizes with TLR4. BLS is mostly processed by the exogenous pathway but a small portion was not associated with this pathway. BLS persists for 96 hours in vitro in a higher amount of dendritic cells in comparison with a control antigen and still persists in cells of the draining lymph node for 14 days post immunization. \nBLS remains in the immunized animal for a longer period than the control antigen, however this probably does not explain the persistence of the humoral response.\nThis work contributes to get a better understanding of the immunological processes that allow BLS to act as a carrier and it might be use as a powerful tool for the development and improvement of vaccine platforms.